Excellence without borders: an interview with Rachael Dangarembizi on conducting globally competitive research in resource-constrained settings (Communications Biology)
Dr. Rachael Dangarembizi is a Senior Lecturer in the Department of Human Biology and a neuroscientist in the Neuroscience Institute at the University of Cape Town in South Africa. She has established the first laboratory in Africa that studies the mechanisms of brain injury caused by fungal neuroinfections. Her research bridges basic science with clinical insights, aiming to improve diagnosis, treatment, and patient outcomes by understanding fungal-host interactions, neuroimmune responses, and brain injury. Dr. Dangarembizi has earned multiple awards for her work and leads several organizations dedicated to advancing neuroscience capacity across Africa with the aim of growing local expertise and infrastructure to drive impactful research. In this Q&A, she tells us about the challenges and opportunities of conducting globally competitive research with limited resources.